3,5-Bis(4-hydroxyphenyl)-4H-1,2,4-triazol-4-amine monohydrate - Silong, Sidik; Ab. Rahman, Mohamad Zaki; Ahmad @ Ayob, Mansor; Kwong, Huey Chong; Ng, Seik Weng (Wiley-Blackwell Publishing, 2010)
The triazole ring in the title compound, C14H12N4O2·H2O, makes dihedral angles of 36.9 (1) and 37.3 (1)° with the two benzene rings. Each hydroxy group is a hydrogen-bond donor to a two-coordinate N atom of an adjacent molecule; these O—H⋯N hydrogen bonds generate a layer parallel to the ab plane. Adjacent layers are linked by N—-H⋯O and Owater—H⋯O hydrogen bonds into a three-dimensional network.